SEASONAL EFFECT ON SEMEN CHARACTERISTICS OF MURRAH BUFFALO BULLS RAISED UNDER TROPICAL CLIMATE - Isnaini, Nurul; Harsi, Tri; Maharani, Devi (Jurnal Kedokteran Hewan, 2019)
This study was carried out to evaluate the seasonal variation on semen characteristics of Murrah buffalo bulls in Indonesia. A total of three Murrah buffalo bulls were included in this study. The semen was collected once a week during the rainy season (from January to April and from October to December) and the dry season (from May to September). Immediately after collection, the semen volume, sperm concentration, total sperm output, individual motility, post-thawing motility, and straw production were evaluated. The results showed that the season did not change (P0.05) the semen volume, individual motility, and post-thawing motility. However, sperm concentration, total sperm output, and straw production were decreased in the dry season (P0.05) as compared to the rainy season. In conclusion, several semen characteristics of Murrah buffalo bulls may vary depending on the season of collection. The semen collection during the rainy season is more profitable than the dry season.